Effects of annealing on the properties and structure of electrodeposited semiconducting Cu?O thin films - Wijesundera, R.P.; Hidaka, M.; Koga, K.; Sakai, M.; Siripala, W.; Choi Jae-Young; Sung, N.E. (Physica Status Solidi (basic solid state physics), 2007)
The structures and the electronic states in electrodeposited semiconductor Cu?O thin films have been investigated for each annealing temperature (TA) by X-ray diffraction (XD) and X-ray absorption spectroscopy (XAS) near the Cu K edge using synchrotron radiation. The thin films prepared as grown and annealed at TA ? 175 C, 200 C ? TA ? 300 C, TA = 400 C are characterized mainly by the pure Cu2O-type structure, the pseudo-Cu2O-type having a superlattice structure, and two phases of Cu2O-type and CuO-type structures, respectively, while the film annealed at TA = 500 C is single-phase CuO-type. The XAS spectra suggest that there is a structural phase transition occurring at about 400 C, which induces a modulation of the local structure around Cu ions observed in the extended X-ray absorption fine structure (EXAFS) and the occupational electronic band states of Cu-4p localized just above the Fermi level, taken from X-ray absorption near edge structure (XANES). The open-circuit voltage suggests that the photosensitivity of the Cu?O thin films strongly depends on the annealing treatment and shows a crossover from an n-type to a p-type semiconductor. (? 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)